Correction: Separation of micro-phytoplankton from inorganic particulate in Antarctic seawater (Ross Sea) for the determination of Cd, Pb and Cu: optimization of the analytical methodology. Issue 16 (21st August 2015) - Truzzi, C.; Annibaldi, A.; Finale, C.; Libani, G.; Romagnoli, T.; Scarponi, G.; Illuminati, S.
<x xml:space="preserve">Abstract</x> Correction for 'Separation of micro-phytoplankton from inorganic particulate in Antarctic seawater (Ross Sea) for the determination of Cd, Pb and Cu: optimization of the analytical methodology' by C. Truzzi et al., Anal. Methods, 2015, 7, 5490–5496.